(untitled) (Experimental biology, 2015)
Study of the enzymatic activity of pathogenic fungi important because it can identify certain patterns in the induction of protective properties of plants. Enzymes play an important role in the life of plants and fungi . Pathogenic properties of plant pathogens are largely due to their ability to produce hydrolytic enzymes . Enzymes , the ability of pathogens to penetrate the plant tissue , destroy cellular structures . Ability of microscopic fungi produce enzymes may indicate their pathogenicity . We studied the enzymatic activity ( cellulolytic and amylolytic ) strains of the fungus D. tritici-repentis Dtr 3/ 04 and Dtr 6 /04 because it is the enzymes play a key role in the development of plant diseases, they are essential elements of pathogenesis, are catalysts for the synthesis of a number of biologically active substances pathogens.